2010
DOI: 10.1128/jcm.00147-10
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Blood PCR in Combination with Blood Cultures for Improvement of Microbiological Documentation of Infection in Febrile Neutropenia

Abstract: The frequent lack of microbiological documentation of infection by blood cultures (BC) has a major impact on clinical management of febrile neutropenic patients, especially in cases of unexplained persistent fever. We assessed the diagnostic utility of the LightCycler SeptiFast test (SF), a multiplex blood PCR, in febrile neutropenia. Blood for BC and SF was drawn at the onset of fever and every 3 days of persistent fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 43 publications
4
65
0
6
Order By: Relevance
“…This is comparable to the results of some earlier studies [26,27]. In studies performed in emergency departments, the rates of positivity were generally higher.…”
Section: Streptococcus Constellatussupporting
confidence: 89%
“…This is comparable to the results of some earlier studies [26,27]. In studies performed in emergency departments, the rates of positivity were generally higher.…”
Section: Streptococcus Constellatussupporting
confidence: 89%
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
“…60,64,70,71,75,76,79,83,[85][86][87][92][93][94][95][96]107,110,112 Of these, one used the BACTEC system with MALDI-TOF MS. 112 Seventeen studies reported using the BacT/ALERT system. 45 70,75,83,99,109 For the remainder of the studies evaluating SeptiFast against blood culture (with or without MALDI-TOF MS) the unit of analysis was samples. Although the heterogeneity in the metrics has the potential to introduce some bias, the impact on the results was believed to be modest.…”
mentioning
confidence: 99%
“…Since their sensitivity is significantly lower once antibiotic therapy has been started, they should be performed immediately when infection during neutropenia is suspected. 120 Hopefully, novel diagnostic methods, mostly based on Polymerase Chain Reaction (PCR) systems, will improve the yield of blood cultures, particularly if drawn after the onset of antibiotic therapy, such as in case of persistent fever, and will result in shorter time to microbiological diagnosis. 120 Furthermore the combination of nucleic acids amplification with mass spectrometry could permit obtaining the results within 6 hours, but no data are so far available in hematology or oncology settings.…”
Section: Diagnosismentioning
confidence: 99%
“…120 Hopefully, novel diagnostic methods, mostly based on Polymerase Chain Reaction (PCR) systems, will improve the yield of blood cultures, particularly if drawn after the onset of antibiotic therapy, such as in case of persistent fever, and will result in shorter time to microbiological diagnosis. 120 Furthermore the combination of nucleic acids amplification with mass spectrometry could permit obtaining the results within 6 hours, but no data are so far available in hematology or oncology settings. 121 In non-neutropenic patients, procalcitonin (PCT) is used as an early serum marker of inflammation (it increases within 3 hours from infection, compared to 24 hours for C-reactive protein, CRP), as it has over 90% sensitivity and specificity for bacterial BSI.…”
Section: Diagnosismentioning
confidence: 99%